Full Efficiency Recovery in Hole-Transporting Layer-Free Perovskite Solar Cells With Free-Standing Dry-Carbon Top-Contacts - Valastro, Salvatore; Smecca, Emanuele; Sanzaro, Salvatore; Deretzis, Ioannis; La Magna, Antonino; Numata, Youhei; Jena, Ajay Kumar; Miyasaka, Tsutomu; Gagliano, Antonio; Alberti, Alessandra (Frontiers in Chemistry, 2020)
Carbon-based top electrodes for hole-transporting-layer-free perovskite solar cells (PSCs) were made by hot press (HP) transfer of a free-standing carbon-aluminum foil at 100°C and at a pressure of 0.1 MPa on a methylammonium lead iodide (MAPbI3) layer. Under these conditions, the perovskite surface was preserved from interaction with the solvent. Over a timescale of 90 days, HP-PSCs were systematically compared to reference cells with carbon-based top electrodes deposited by doctor blading (DB). We found that all the photovoltaic parameters recorded in HP-PSCs during time under ambient conditions settled on values systematically higher than those measured in the reference DB-PSCs, with efficiency stabilized at around 6% within the first few measurements. On the other hand, in DB-PSCs, a long-lasting (~14 days) degrading transient of the performances was observed, with a loss of efficiency from an initial ~8% to ~3%. Moreover, in HP-PSCs, a systematic day-by-day recovery of the efficiency after operation was observed (Δ~2%) by leaving the cell under open circuit, a nitrogen environment, and dark conditions. Noteworthily, a full recovery of all the parameters was observed at the end of the experiment, while DB-PSCs showed only a partial recovery under the same conditions. Hence, the complete release of solvent from the carbon contact, before an interface is established with the perovskite layer, offers a definite advantage through the long period of operation in preventing irreversible degradation. Our findings indeed highlight the crucial role of the interfaces and their feasible preservation under nitrogen atmosphere.